Comprehensive Production Maintenance and its Role in Improving the Company Performance - Kareem, Jasim Mohammed; Alallaq, Hussein Adnan Essa; Alsaedi, Rafid Khudhur Radhi; Al-Jazaeri, Mohammed Basim Mohammed; Sabti, Yousif Mousa (South Asian Journal of Social Sciences and Humanities, 2023)
The study aimed to reveal the impact of applying comprehensive production maintenance on company performance in small and medium industrial Malaysian companies. The descriptive analytical secondary data was utilised as a tool for gathering data from 135 companies as a sample from 2009 to 2017, and after conducting the analysis of the data and testing the hypotheses, the study reached a number of results among them. There is a positive significant effect of the application of comprehensive productivity maintenance on company performance in in the small and medium industrial companies. Therefore, this study recommended that the total productive maintenance is a system that is also valuable for quality administration and safety administration in rapports of keeping the integrity of equipment and operating approaches. The study recommended giving more attention to the management of the industrial companies.